Sumbangan Syeikh Muhammad Saleh Abdullah Minangkabawi : The Contributions of Sheikh Muhammad Saleh Abdullah Minangkabawi - Mat Jusoh, Mohd Zulfakar; Saari, Che Zarrina; Zainal Abidin, Azmil (Journal Al-Muqaddimah, 2021)
The development of Islam in the state of Perak was not popular in the 19th century. After the presence of figure from Minangkabawi such as Sheikh Muhammad Saleh Abdullah Minangkabawi, the development of religious discourse was getting more positive. Generally, Sheikh Muhammad Saleh Abdullah was one of the scholars who played a role in spreading Islamic teachings in the form of Sufism in the natural archipelago. He was appointed as Sheikh al-Islam Perak Darul Ridzuan by Yamtuan Muda Perak. This article used a data collection survey method and historical based analysis which were applied to the contributions brought by Sheikh Muhammad Saleh Abdullah Minangkabawi as Sheikh al-Islam Perak Darul Ridzuan. The result of this study found that Sheikh Muhammad Saleh Abdullah succeeded in spreading the teachings by using a position in politics as an influential person with the Sultanate of Istana Perak Darul Ridzuan. Inculcating positive dimensions for the influence of tasawwuf knowledge in the Malay archipelago was also one of the contributions made by Sheikh Muhammad Saleh Abdullah Minangkabawi.